1994
DOI: 10.1161/01.cir.89.3.1301
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation guided by intracardiac echocardiography.

Abstract: Background Radiofrequency catheter ablation requires precise positioning of the ablation electrode. Fluoroscopically guided catheter manipulation has limitations, and there are risks of radiation exposure. The purpose of this study was to examine the feasibility of guiding catheter ablation within the right atrium with catheter-based intracardiac echocardiography.Methods and Results A 10F, 10-MHz intracardiac imaging catheter was used to direct an ablation electrode at four or five anatomic landmarks in the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 14 publications
1
59
0
1
Order By: Relevance
“…19,20 In animals subjected to radiofrequency catheter ablation, the lesion size noted with intracardiac ultrasound correlates well with the lesion size observed postmortem. 20 In the present study, diagnostic ultrasound was used to select ablation target sites and to monitor …”
Section: Imaging Of Ablation Targets and Lesionssupporting
confidence: 54%
“…19,20 In animals subjected to radiofrequency catheter ablation, the lesion size noted with intracardiac ultrasound correlates well with the lesion size observed postmortem. 20 In the present study, diagnostic ultrasound was used to select ablation target sites and to monitor …”
Section: Imaging Of Ablation Targets and Lesionssupporting
confidence: 54%
“…Several studies have demonstrated the utility of intracardiac ultrasound for guiding cardiac ablation therapy [11][12][13] and visualizing thermal lesions in vitro. 10,14 A recent study by Epstein and colleagues 15 compared intracardiac ultrasound to fluoroscopy guidance for creating linear right atrial lesions in a canine model and showed that intracardiac ultrasound significantly improved targeting, energy delivery, and lesion formation.…”
Section: Comparison With Other Imaging Modalitiesmentioning
confidence: 99%
“…It usually occurs at the site with the highest temperature (the surface of the heated tissue) and has poor adherence to the ablation electrode and transeptal sheaths. 8 Such a formation may only be noticeable with intracardiac echocardiography (ICE), because it may not be associated with impedance rises 9, and occurs even in patients submitted to increased intensity anticoagulation protocols. [10][11][12] Some studies have shown that more aggressive heparinization strategies during the procedure results in a reduction of embolic complications.…”
Section: Soft Thrombus Formationmentioning
confidence: 99%